Exome sequencing identifies a de novo SCN2A mutation in a patient with intractable seizures, severe intellectual disability, optic atrophy, muscular hypotonia, and brain abnormalities. Issue 4 (1st March 2014) - Baasch, Anna‐Lena; Hüning, Irina; Gilissen, Christian; Klepper, Joerg; Veltman, Joris A.; Gillessen‐Kaesbach, Gabriele; Hoischen, Alexander; Lohmann, Katja
Summary Epilepsy is a phenotypically and genetically highly heterogeneous disorder with >200 genes linked to inherited forms of the disease. To identify the underlying genetic cause in a patient with intractable seizures, optic atrophy, severe intellectual disability (ID), brain abnormalities, and muscular hypotonia, we performed exome sequencing in a 5‐year‐old girl and her unaffected parents. In the patient, we detected a novel, de novo missense mutation in the SCN2A (c.5645G>T; p.R1882L) gene encoding the αII‐subunit of the voltage‐gated sodium channel Nav1.2. A literature review revealed 33 different SCN2A mutations in 14 families with benign forms of epilepsy and in 21 cases with severe phenotypes. Although almost all benign mutations were inherited, the majority of severe mutations occurred de novo. Of interest, de novo SCN2A mutations have also been reported in five patients without seizures but with ID (n = 3) and/or autism (n = 3). In the present study, we successfully used exome sequencing to detect a de novo mutation in a genetically heterogeneous disorder with epilepsy and ID. Using this approach, we expand the phenotypic spectrum of SCN2A mutations. Our own and literature data indicate that SCN2A‐linked severe phenotypes are more likely to be caused by de novo mutations. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.